French Presidential Elections - Lewis-Beck, M. author. aut Link
XIX, 232 p.
Keywords: An original and comprehensive study of the sociological and psychological forces driving individual choices in French Presidential elections. Based on a unique comparative analysis of four French presidential contests over the last two decades, this book presents a rigorous examination of long-term and short-term voter motivations.